Bee Venom Therapy: An Ethical of Islamic Perspective - Asni, Fathullah; Harun, Mohammad Amir Wan (Human Resource Management Academic Research Society, 2020)
Bee venom therapy (BVT) is one of the traditional methods of medicine that has been practiced since 1000-3000 BC. BVT has been used for many diseases, especially rheumatoid arthritis, Parkinson’s disease, and others in clinical treatment. However, this treatment method has raised questions based on the Prophet’s hadith which stated Islam as a religion that forbids the killing of bees as a result of using their venom. Therefore, this paper aims to study the practice of BVT from the ethical point of Islamic treatment. This qualitative study collected its data through library research, i.e. by referring to Islamic ethics therapy and BVT practices from books and journals. The data were analysed using document and content analysis. The study found that Islamic ethics treatment permitted the treatment of bee venom (BV) with four conditions, namely get advice from a medical professional, no alternative medicine for the disease encountered, treatment only when needed, and no allergic reaction to BV. This is because some studies are claiming that BVT can gives adverse effects on patients if there is no guidance provided by a specialist. Therefore, the advice of a specialist in BVT is important to prevent any harm to the patient.